Low Temperature Delays Metabolism of Quizalofop in Resistant Winter Wheat and Three Annual Grass Weed Species - Bough, Raven A.; Gaines, Todd A.; Dayan, Franck E. (Frontiers in Agronomy, 2022)
Quizalofop-resistant wheat is the core component of the recently commercialized CoAXium™ Wheat Production System. As with other herbicides, quizalofop provides better weed control at early growth stages and under optimum temperature. However, in regions with winter wheat production, quizalofop application may be affected by unpredictable, rapid temperature decreases. Temperature shifts can cause crop injury or impact weed control efficacy. In the following study, we examine the effect of reduced temperature on quizalofop content and metabolism in CoAXium™ winter wheat and three winter weed species: downy brome (Bromus tectorum L.), feral rye (Secale cereale L.), and jointed goatgrass (Aegilops cylindrica Host). Temperature conditions include either 19°C or 4.5°C daytime temperatures with tissue sampling over 5 timepoints (1 to 16 or 18 days after treatment, DAT). Analysis features liquid chromatography coupled to tandem mass spectrometry detection of the active form of quizalofop, quizalofop acid. Quizalofop content trends reveal delayed metabolism under cooler conditions for wheat and weeds. Quizalofop content peaks within 1 to 2 DAT in the warmer temperatures for all species and decreases thereafter. In contrast, content peaks between 8 and 9 DAT at cooler temperatures except for downy brome. Minimal decreases in content over time generally follow cooler temperature peaks. Further, the absence of differences in maximum quizalofop content in all species suggests absorption and/or de-esterification of quizalofop proherbicide to the active form is not reduced at cooler temperatures. Final dry shoot tissue biomass does not necessarily correspond to differences in metabolism, as biomass of wheat treated with a field rate of quizalofop does not differ between temperatures. Weeds were treated with sublethal doses of quizalofop in order to monitor herbicide metabolism without causing plant death. Under this condition, weed biomass only differs for jointed goatgrass, which has a greater biomass in the cooler temperature.